Lamb's plane problem in a thermo-visco-elastic micropolar medium with the effect of gravity. (1992) - Das, Pravangsu Sekhar; Sengupta, P. R.; Debnath, Lokenath
Abstract : A study is made of the Lamb plane problem in an infinite thermo-visco-elastic micropolar medium with the effect of gravity. The visco-elasticity is characterized by the rate dependent theory of micro-visco-elasticity generalizing the classical Kelvin-Voigt theory. The action of time harmonic loading is treated in detail. The solutions for the displacement fields, couple stresses and the temperature field are obtained in general and particular cases.